Pengaruh Metode Repetisi dan Metode Interval Intensif Terhadap Kecepatan Renang Gaya Bebas 50 Meter (Studi Eksperimen Pada Atlet Klub Profi Swimming Kota Padang) - surahman, fadli (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2016)
Abstract: Based on the observations of the researcher in the field showed that the Athlete of Profi Swimming Padang still have low speed in swimming 50 meters, Therefore, this study aimed at observing the effect of repetition method and interval intensive method toward 50 meters speed achievement. Type of the research was quasi-experimental (Quasy experiment). this research was began in may and Juni. The population athlete in Profi Swimming Padang in the age group III and IV age group as many as 19 people, while the sample of this research were KU III and KU IV of totally 16 people by purposive sampling technique. The instrument which used in this research was a test of speed in 50 meter sprint achievement. The data was analysed by using t-test uji-t (dependent sample and dependent sample). The results of data analysis show that: (1) There are influences repetition method which significantly to the speed of 50 meters freestyle swimming in athletes Profi Padang be obtained the value of t count = 12,22> t table = 1,90, (2) There are influences interval intensive method which significantly to the speed of 50 meters freestyle swimming in athletes Profi Padang be obtained the value of t count = 10,09> t table = 1,90, (3) Repetition method is more better than series of interval intensive method to the speed of 50 meters freestyle swimming in athletes Profi Padang be obtained the value of t count = 0,30 < t table = 1,76. Key word: Repetition Method and Interval Intensive Method and Sprint 50 meters